The economic burden of loiasis: A comprehensive cost-of-illness analysis of regionally representative, individual-level data from rural Gabon - Cédric Isaac Mbavu; Kerstin Perlik; Tom Stargardt; Selidji Todagbe Agnandji; Olouyomi Scherif Adegnika; Rella Zoleko-Manego; Michael Ramharter; Jan Priebe (PLoS ONE, 2026)
Loiasis is a vector-borne filarial infection endemic to parts of sub-Saharan Africa. It disproportionally affects economically disadvantaged communities in rural, forested regions. To better understand the economic burden of loiasis, we conducted a comprehensive cost-of-illness study in an endemic region of Gabon, with the aim of quantifying the financial costs incurred by individuals infected with the disease from a societal perspective. We conducted a cross-sectional survey in 2023 in rural Gabon. Study participants took part in diagnostic testing for loiasis and were interviewed based on a standardized questionnaire covering a wide range of medical and non-medical costs. Participants reporting eye worm migration or harboring loiasis microfilariae were defined as loiasis positive. Various cost estimates were derived by creating a synthetic control group by means of entropy-balancing and then applying generalized linear models (GLM) for the study region. We show that the average annual costs directly attributable to loiasis amount to 39.94 USD per individual per year. Average cost estimates are primarily driven by indirect costs and direct non-medical costs. We further show that in the rarer cases that individuals seek treatment at formal or informal healthcare providers for loiasis-specific symptoms, costs from the patient’s perspective can be excessively high and amount to about 43 percent of the average monthly per capita income in the study region.